Compostable capsule and preparation thereof

By applying a coating containing amylose and fatty acids on the coffee powder press, the problem of difficult to guarantee dimensional accuracy and sealing properties of existing compostable capsules during processing is solved, and a higher quality beverage preparation is achieved.

CN119894382APending Publication Date: 2025-04-25DELICA AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380069945.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-10-31
Filing Date
2023-10-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing compostable capsules are difficult to ensure dimensional accuracy and sealing profile during processing, which affects the quality of beverage preparation.

Method used

Using coating technology containing amylose and fatty acids, coated onto the pressed blank of coffee powder or powder mixture to form a waxy substance to improve moisture-proof layer and dimensional stability.

Benefits of technology

The dimensional accuracy and sealing of compostable capsules are achieved, and the quality and stability in the beverage preparation process are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894382A_ABST
    Figure CN119894382A_ABST
Patent Text Reader

Abstract

The present invention relates to a capsule, in particular for preparing a beverage by introducing water into the capsule. The capsule comprises a compact of a powder or powder mixture. The compact is coated with at least one layer comprising at least one starch and at least one fatty acid. The at least one starch is an amylose-containing starch, preferably having an amylose content (w / w) of 10% to 40%, preferably 14% to 40%, most preferably 14% to 25%. The invention also relates to a method for preparing such a capsule and to the use of such a capsule.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] According to the features of the general terms of the independent claims, the invention relates to compostable capsules and to a method for preparing such capsules and to the use of such capsules.

[0002] It is well known to provide premium food products such as coffee in capsule form. However, materials commonly used as packaging materials, such as plastic or aluminum (eg EP 0 468 079 A1 ), have the disadvantage that they can only be recycled with difficulty and are generally not compostable.

[0003] Biodegradable coffee capsules are known. DE 10 2018 2011 87 B3 describes a capsule made of a wood material composited with a bioplastic. However, a problem with such capsules made of compostable material is their processing. Although these capsules can be manufactured using injection molding technology depending on the material used, dimensional accuracy is difficult to ensure due to the high fiber content. In particular, it is difficult to form the sealing profile with low tolerances, which allows the preparation of beverages under high pressure.

[0004] DE102014000187B4 describes another biodegradable capsule made of a coffee powder compact coated with a biodegradable layer. For this purpose, the coffee compact is preferably coated with liquid cellulose made of polysaccharides, a polyol spacer and a crosslinking agent. DE102014000187B4 also mentions a coating of plant starch and fatty acids, but does not provide any information on the details of the starch type, fatty acid type or mixing ratio.

[0005] Therefore, one object of the present invention is to overcome the disadvantages of the prior art. In particular, a capsule for preparing a beverage is provided, which is compostable. Another object of the present invention is to provide a method and use for such a capsule.

[0006] These objects are solved by the device and the method defined in the independent patent claims. Further embodiments are indicated in the dependent claims.

[0007] A first aspect of the present invention relates to a capsule, in particular a capsule for preparing a beverage by introducing water into the capsule. The capsule comprises a compact of a powder or a powder mixture, the compact being coated with at least one layer comprising at least one starch and at least one fatty acid. The at least one starch of the coating is an amylose-containing starch, preferably having an amylose content (w / w) of 10 to 40%, preferably 14 to 40%, most preferably 14 to 25%. Surprisingly, the results show that not all starches are suitable for preparing a coating for capsules. Instead, it was found that the starch must have a certain amylose content. Amylose-free starches, such as waxy maize starch or waxy rice starch, do not produce a homogeneous film for applying the coating to the compact.

[0008] The green compact is at least partially, preferably completely, coated with at least one layer. This protects the green compact as much as possible from moisture.

[0009] The capsule can be understood as a compact with at least one layer, or the compact can be additionally coated with a compostable capsule body, for example a capsule body made of cellulose. In the second case, at least one layer of starch and fatty acids is preferably applied to the capsule body, increasing the dimensional stability during beverage preparation and improving the barrier properties to oxygen and moisture. Of course, in the case of an additional capsule body, it is conceivable that the powder or powder mixture is present as bulk material instead of the compact. The following remarks on the coating apply equally to the coated compact and the coated capsule body.

[0010] According to the invention, a "pressed green" is understood to be a core material that is compacted under pressure. According to the invention, it is advantageous to provide the core material of the capsule in the form of a pressed green if the core material is at least partially coated by impregnation, coating or spraying with a coating according to the invention, so that the core material does not disintegrate during the coating process. Therefore, the core material preferably has a certain strength. This can preferably be achieved by compacting the core material with a compression pressure in the range of 1-100 MPa, preferably 5-50 MPa, so that the resulting pressed green has a strength in the range of 3-120 N, preferably 5-60 N. The compression pressure applied for the manufacture of the pressed green depends on the properties of the core material, for example in the case of coffee powder, on the degree of grinding, degree of roasting and moisture content of the powder. In particular in the case of coffee powder, it can be observed that powders with a lower fat or oil content, such as decaffeinated coffee powder or coffee powder with a light roasted color, require higher compression pressures to obtain stable pressed greens.

[0011] The strength of the compact is determined by placing the compact between two plates of a compression tensile testing machine (for example equipped with an Xforce P force sensor from Zwick / Roell) and measuring the force required to crush the compact. This method is also described in WO 2008 / 123775 A1, page 3.

[0012] The at least one layer may comprise at least one polyol, which is preferably selected from the group consisting of: aliphatic polyols, preferably ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, erythritol, xylitol, most preferably sorbitol and glycerol; cyclic polyols, preferably glucose, fructose, mannose, galactose, oligofructose, inulin, isomaltulose, trehalose; sugar substitutes, preferably mannitol, isomalt, maltitol, lactitol; and aromatic polyols, preferably cyanidin, corilagin, digallic acid, tannic acid and gallic acid; and combinations thereof.

[0013] The polyols make the film forming the coating easier to apply. The film is less brittle and therefore less prone to cracking after drying. The polyols also prevent the beverage from forming greasy residues on it after preparation.

[0014] Surprisingly, it has been found that fatty acids and polyols react at least partially with each other to form mono-fatty acid esters. Mono-fatty acid esters are insoluble in water and form waxy substances. This further improves the moisture barrier of the coating.

[0015] Preferably, the at least one fatty acid is selected from the group consisting of palmitic acid, stearic acid, oleic acid, linoleic acid, gamma-linoleic acid, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and combinations thereof. EPA and DHA are particularly preferred in compacts made from powder mixtures containing milk powder.

[0016] The at least one fatty acid enables the film to be applied to form a coating. The fatty acid prevents the liquid coating medium from penetrating into the compact.

[0017] Advantageously, the at least one starch is selected from the group consisting of: cereal starches, preferably corn starch, wheat starch, rye starch, barley starch, millet starch, oat starch, potato starch, tapioca starch, pea starch; and combinations thereof. These starches have an ideal amylose content. Tests with waxy corn starch or waxy rice starch are difficult to handle, as they contain no amylose or have only a very low amylose content.

[0018] The ratio (w / w) of starch to fatty acid in the layer may be 15.0: 1.0 to 2.0: 1.0, preferably 10.0: 1.0 to 4.0: 1.0, particularly preferably 7.0: 1.0 to 5.0: 1.0. At a ratio of 15.0: 1.0, the solution to be applied is very viscous, but still just applicable. At a ratio of 2.0: 1.0 to 4.0: 1.0, the fluidity of the solutions is very good, so that they are still just applicable, depending on the intensity of use. A ratio of 10.0: 1.0 to 4.0: 1.0 is ideal, because the corresponding solution is easy to apply and a uniform application amount and appearance are obtained.

[0019] A ratio of starch to fatty acid of 6.6:1.0 or 5.0:1.0 is particularly preferred and gives the best results in terms of coating quality and layer suitability.

[0020] The ratio (w / w) of starch, fatty acid and polyol in the layer can be 15.0: 1.0: 15.0 to 2.0: 1.0: 0.1, preferably 10.0: 1.0: 10.0 to 4.0: 1.0: 0.5, particularly preferably 7.0: 1.0: 7.0 to 5.0: 1.0: 1.0. The ratio is selected in such a way that the corresponding solution can be applied optimally and is neither too thin nor too viscous.

[0021] A ratio of starch:fatty acid:polyol of 6.6:1.0:1.6 is particularly preferred and gives the best results with regard to coating quality and layer suitability for the mixture with polyol.

[0022] Preferably, the capsule has from 1 to 100 layers, preferably from 2 to 50 layers, most preferably from 2 to 10 layers.

[0023] The capsule may also have at least one layer of a cross-linked polysaccharide. The application of such an additional layer increases the stability of the compact and additionally protects it from oxygen. The at least one layer of a cross-linked polysaccharide is preferably applied on a layer of at least one starch and at least one fatty acid or between two layers of at least one starch and at least one fatty acid. Of course, the same layer arrangement is also possible for the coated capsule body.

[0024] Preferably, the cross-linked polysaccharide is formed by a polysaccharide and at least one cross-linking agent. Advantageously, the polysaccharide is selected from the group comprising: alginate, carrageenan, cellulose, cellulose derivatives, chitin, chitosan, pectin, guar gum, xanthan gum, locust bean gum, gum arabic, pullulan and agar; and combinations thereof. Polysaccharides having good food compatibility are preferred.

[0025] Such polysaccharides are readily available, often of natural origin, and are therefore sustainable and can also be easily biodegraded.

[0026] The at least one crosslinking agent may be selected from compounds having one or more carbonyl functional groups and / or carboxyl functional groups, in particular dialdehyde compounds, diketone compounds and dicarboxylic acids, tricarboxylic acids or tetracarboxylic acids; and combinations thereof. The diketone compound may be a 1,2-diketone, preferably 2,3-butanedione, 2,3-pentanedione and 2,3-hexanedione. The at least one crosslinking agent may also be a divalent cation or a higher valent cation, in particular a salt of an alkaline earth metal cation, most preferably CaCl2.

[0027] However, the cross-linked polysaccharide may also be a naturally cross-linked polysaccharide. For example, cellulose is cross-linked to each other to form a fibrous structure.

[0028] Capsules having at least one layer of corn starch, stearic acid and optionally glycerol or sorbitol are also preferred.

[0029] Capsules comprising at least one layer of corn starch, palmitic acid and glycerol are also preferred.

[0030] Capsules consisting of at least one layer of pea starch, stearic acid and glycerol are also preferred.

[0031] Capsules comprising at least one layer of rice starch, stearic acid and glycerol are also preferred.

[0032] It is also possible that the capsule comprises a coating of several layers and mixtures of the aforementioned layers.

[0033] It is also conceivable that in addition to or instead of starch, at least one cross-linked polysaccharide (preferably as described above) and at least one fatty acid may be combined. In particular, in combination with a polyol (preferably as described above), forming a water-insoluble mono-fatty acid ester, the moisture barrier of the coating can be improved. This protects the pressed green compact from water absorption, in particular.

[0034] Advantageously, the powder or powder mixture is selected from the group consisting of: coffee, coffee blends, coffee substitute blends, tea, tea blends, cocoa, cocoa blends, drinking chocolate, milk powder, milk coffee blends, fruit milk, vegan milk substitute, instant coffee, coffee substitute products and dry soups, and combinations thereof.

[0035] Preferably, the capsule has a rounded, in particular spherical shape. However, it is also conceivable that the shape of the capsule substantially corresponds to other geometric bodies, such as a cube, a cuboid, a prism, a pyramid, a cylinder, a truncated cone, a cone, a torus, an ellipsoid, etc. It should be noted that any corners and edges are preferably not sharp, but rounded.

[0036] Another aspect of the present invention relates to a method for preparing a capsule, in particular a method for preparing a beverage by introducing water into the capsule, in particular the above-mentioned capsule. The method comprises the following steps:

[0037] a) providing a compact made from a powder or a powder mixture,

[0038] b) applying a formulation comprising at least one starch and at least one fatty acid to the compact, wherein the at least one starch is an amylose-containing starch,

[0039] c) drying the formulation to produce a coating.

[0040] In the case of an additional compostable capsule body, a method for preparing a capsule, in particular a method for preparing a beverage by introducing water into said capsule, in particular the above-mentioned capsule, may comprise the following steps:

[0041] a) providing a compostable capsule body, preferably made of cellulose,

[0042] b) applying a formulation comprising at least one starch and at least one fatty acid to the compact, wherein the at least one starch is an amylose-containing starch,

[0043] c) drying the preparation to produce a coating,

[0044] d) filling the coated capsule bodies obtained in step c) with bulk material or pressed green sheets, preferably the above-mentioned powder or powder mixture,

[0045] e) closing the capsule body.

[0046] Unless otherwise stated, the following explanations apply equally to both methods.

[0047] The formulation is preferably in the form of a solution. The starch and the fatty acid may be selected from the group described above for the capsule.

[0048] The formulation may additionally comprise a polyol, which is preferably selected from the group consisting of: aliphatic polyols, preferably ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, erythritol, xylitol, most preferably sorbitol and glycerol; cyclic polyols, preferably glucose, fructose, mannose, galactose, oligofructose, inulin, isomaltulose, trehalose; sugar substitutes, preferably mannitol, isomalt, maltitol, lactitol; and aromatic polyols, preferably cyanidin, corilagin, digallic acid, tannic acid and gallic acid; and combinations thereof.

[0049] The preparation may contain the at least one starch in a concentration of 0.5% to 25.0%, preferably 1.0% to 10.0%, particularly preferably 2.0% to 8.0%.

[0050] The concentration causes the starch to gelatinize into a film, thereby forming a layer.

[0051] The preparation may contain the at least one fatty acid in a concentration of 0.1% to 3.0%, preferably 0.2% to 2.0%, particularly preferably 0.3% to 1.0%.

[0052] Surprisingly, it was found that if the preparation containing fatty acids is left to stand, it thickens. The optimum viscosity of the solution for application is achieved with the specified concentration. Excessive turbidity of the fatty acid solution is prevented. However, the solution should be applied to the compact within 24 hours after preparation.

[0053] Advantageously, the preparation contains the at least one polyol in a concentration of 0.1% to 4.0%, preferably 0.5% to 3.0%, particularly preferably 1.0% to 2.0%.

[0054] When a polyol is added, the mixture of starch solution and fatty acid is additionally stabilized, so that the polyol functions as a mediator.

[0055] Preferably, the formulation is prepared by mixing the at least one fatty acid and the at least one starch simultaneously in water, preferably simultaneously with at least one polyol, followed by heating.

[0056] Simultaneous mixing means that the starch is gelatinized only after everything has been added. For example, the starch can be mixed with water first, with or without the polyol, and heated. The fatty acid is then added and gelatinization occurs.

[0057] Alternatively, the formulation is prepared by gradually mixing the at least one starch in water, followed by heating, followed by the addition of the at least one fatty acid and preferably at least one polyol.

[0058] In this process, the starch is gelatinized before the other ingredients are added. For example, the starch can first be mixed with water and gelatinized at high temperature.

[0059] Therefore, starch gelatinization is preferably carried out before application in step b). Starch gelatinization is usually carried out at a temperature of 50° C. to 90° C. However, in theory, the gelatinization temperature depends on the selected starch and should be higher than the gelatinization temperature of the selected starch.

[0060] Ideally, whether simultaneous mixing or stepwise mixing is chosen, the temperature of the mixture is above the melting temperature of the corresponding fatty acid when the fatty acid is added.

[0061] In the case of coated green compacts, the green compacts obtained after step b) may have a high degree of stickiness. For optimal drying of the coating without damaging the coating due to stickiness, the following steps may be adopted: i) during the drying process, the coated green compacts may be moved in step c); ii) the coated green compacts may be dried very quickly; iii) the coated green compacts may be wiped from the outside to remove powder; iv) the green compacts may be cooled or frozen; and v) the green compacts may be purged with compressed air.

[0062] In case of i), for example, the coated green compacts can be rolled on a mesh belt and do not stick in the drying oven. In ii), the green compacts can be dried briefly at a very high temperature. The powder in iii) can be coffee. For example, it can be coffee residues from the production process. Dust removal prevents the green compacts from sticking in the drying oven.

[0063] "Rapid" in step ii) is understood to mean a drying time of less than 10 minutes, preferably less than 5 minutes, particularly preferably at most 2 minutes at a temperature of preferably more than 100° C. Thus, the surface dries very quickly and can therefore be dried to the final moisture content without damage at a moderate temperature of preferably less than 100° C., preferably 70-85° C., particularly preferably 75 to 85° C.

[0064] Steps b) and c) can be repeated to apply several layers. Preferably, steps b) and c) are performed 1 to 100 times, more preferably 2 to 50 times, most preferably 2 to 10 times. This applies both to the coating of the compacts and to the coating of the capsule bodies.

[0065] An aspect of the present invention also relates to a capsule manufactured by one of the above methods.

[0066] Another aspect of the present invention relates to use of the above capsule, preferably the capsule prepared by the above method, for preparing a beverage.

[0067] The present invention is explained in more detail below with the aid of examples and drawings. The examples and drawings are for illustrative purposes and should not be understood as limiting. They show:

[0068] FIG. 1 : Green compacts prepared according to Examples 1 to 8 of the present invention.

[0069] FIG. 2 : Green compacts prepared according to Examples 9 to 12 of the present invention. Example

[0070] Preparation of green compacts

[0071] For each of the following examples, spherical compacts for coffee preparation were prepared by compacting 5.7 g of roasted ground coffee powder at a pressure of 30 MPa. The coffee powder had a moisture content of 3.5%. The average particle size of the coffee powder was 400 μm ± 100 μm.

[0072] Example 1

[0073] Thingum 100 (corn starch, 25% amylose) and glycerol were dissolved in deionized water to obtain a concentration of 4% starch and 1% glycerol (w / w). The mixture was then heated at 70°C for 5 minutes. Stearic acid was then added to obtain a 0.6% solution. The mixture was then gelatinized at a high temperature of 90°C for 30 minutes and cooled to room temperature.

[0074] The compact was immersed in the aqueous solution for 6 seconds and dried in an air stream for about 6 minutes at 25° C. The compact was then immersed in the solution for a second time for 6 seconds and then dried at 25° C. for 15 minutes.

[0075] The resulting coated green compact 1 is shown in FIG. 1 .

[0076] Example 2

[0077] Thingum 100 was mixed with deionized water to obtain a 4% starch solution. The starch solution was then gelatinized at a high temperature of 90°C for 20 minutes. Glycerol and stearic acid were then added so that glycerol was present in the form of a 1% solution and stearic acid was present in the form of a 0.6% solution. These were further mixed at a high temperature, i.e., 90°C, for 20 minutes. The solution was then cooled to room temperature.

[0078] The coating of the green compact was carried out according to Example 1. The coated green compact 2 obtained is shown in FIG. 1 .

[0079] Example 3

[0080] Example 3 corresponds to Example 1, except that the glycerol content is 2%.

[0081] The resulting coated green compact 3 is shown in FIG. 1 .

[0082] Example 4

[0083] Rice starch was dissolved in deionized water to obtain a concentration of 4% starch (w / w). The starch solution was then gelatinized at an elevated temperature of 90°C for 20 minutes. Glycerol and stearic acid were then added so that glycerol was present in the form of a 1% solution and stearic acid was present in the form of a 0.6% solution. These were further mixed at an elevated temperature, i.e., 90°C, for 20 minutes. The solution was then cooled to room temperature.

[0084] The compact was immersed in the aqueous solution for 6 seconds and dried in an air stream for about 6 minutes at 25° C. The compact was then immersed in the solution for a second time for 6 seconds and then dried at 25° C. for 15 minutes.

[0085] The resulting coated green compact 4 is shown in FIG. 1 .

[0086] Example 5

[0087] Pea starch (20-22% amylose) was dissolved in deionized water to obtain a starch concentration of 4% (w / w). The starch solution was then gelatinized at an elevated temperature of 90°C for 20 minutes. Glycerol and stearic acid were then added so that glycerol was present in the form of a 1% solution and stearic acid was present in the form of a 0.6% solution. These were further mixed at an elevated temperature, i.e., 90°C, for 20 minutes. The solution was then cooled to room temperature.

[0088] The compact was immersed in the aqueous solution for 6 seconds and dried in an air stream for about 6 minutes at 25° C. The compact was then immersed in the solution for a second time for 6 seconds and then dried at 25° C. for 15 minutes.

[0089] The resulting coated green compact 5 is shown in FIG. 1 .

[0090] Example 6

[0091] Example 6 corresponds to Example 5, wherein the concentration (w / w) of starch is 2% and the concentration of stearic acid is 0.6%.

[0092] The resulting coated green compact 6 is shown in FIG. 1 .

[0093] Example 7

[0094] Example 7 corresponds to Example 2, except that palmitic acid is used instead of stearic acid.

[0095] The resulting coated compact 7 is shown in FIG. 1 .

[0096] Example 8

[0097] Thingum 100 (corn starch, 25% amylose) was dissolved in deionized water to obtain a starch concentration of 4% (w / w). The starch solution was then gelatinized at an elevated temperature of 90°C for 20 minutes. Sorbitol and stearic acid were then added so that sorbitol was present in the form of a 2% solution and stearic acid was present in the form of a 0.6% solution. These were further mixed at an elevated temperature, i.e., 90°C, for 20 minutes. The solution was then cooled to room temperature.

[0098] The compact was immersed in the aqueous solution for 6 seconds and dried in an air stream for about 6 minutes at 25° C. The compact was then immersed in the solution for a second time for 6 seconds and then dried at 25° C. for 15 minutes.

[0099] The resulting coated green compact 8 is shown in FIG. 1 .

[0100] Comparative Example

[0101] Example 9

[0102] Example 9 corresponds to Example 1, with the difference that the solution is prepared without stearic acid.

[0103] The obtained green compact 9 is shown in FIG. 2 .

[0104] Example 10

[0105] Example 10 corresponds to Example 3, but without stearic acid. The resulting compact 10 can be seen in FIG. 2 .

[0106] Embodiment 11

[0107] Thingum 300 (waxy maize starch, 0% amylose) and glycerol were dissolved in deionized water to obtain a concentration of 4% starch and 1% glycerol (w / w). The mixture was then heated to 70°C for 5 minutes. Stearic acid was then added to obtain a 0.6% solution. The mixture was then gelatinized at 90°C for 30 minutes and cooled to room temperature.

[0108] The compact was immersed in the aqueous solution for 6 seconds and dried in an air stream for about 6 minutes at 25° C. The compact was then immersed in the solution for a second time for 6 seconds and then dried at 25° C. for 15 minutes.

[0109] The obtained green compact 11 may be shown in FIG. 2 .

[0110] Example 12

[0111] Example 12 corresponds to Example 11, without stearic acid.

[0112] The resulting green compact 12 may be as shown in FIG. 2 .

[0113] Figure 1 shows coated green compacts according to the invention of Examples 1 to 8. All capsules are spherical in shape and the coating is smooth, mostly shiny and transparent.

[0114] The way the solution was prepared (ie mixed according to eg Example 1 or Example 2) did not play a significant role in the outcome of the coating.

[0115] Figure 2 shows the compacts obtained according to the non-inventive comparative examples 9 to 12. The balls showed cracks and no smooth and glossy coating. The balls coated with the Thingum 300 solution (Examples 11 and 12) showed less sticky behavior after application and also showed cracks in the balls after drying.

Claims

1. A capsule, in particular for preparing a beverage by introducing water into the capsule, comprising a compact of a powder or a powder mixture, the compact being coated with at least one layer comprising at least one starch and at least one fatty acid, characterized in that The at least one starch is an amylose-containing starch, preferably having an amylose content (w / w) of 10 to 40%, preferably 14 to 40%, most preferably 14 to 25%.

2. The capsule according to claim 1, wherein The at least one layer comprises at least one polyol, which is preferably selected from the group consisting of: aliphatic polyols, preferably ethylene glycol, propylene glycol, butylene glycol, triethylene glycol, polyethylene glycol, polypropylene glycol, erythritol, xylitol, most preferably sorbitol and glycerol; cyclic polyols, preferably glucose, fructose, mannose, galactose, oligofructose, inulin, isomaltulose, trehalose; sugar substitutes, preferably mannitol, isomalt, maltitol, lactitol; and aromatic polyols, preferably cyanidin, corilagin, digallic acid, tannic acid and gallic acid; and combinations thereof.

3. The capsule according to any one of the preceding claims, wherein The at least one fatty acid is selected from the group consisting of palmitic acid, stearic acid, oleic acid, linoleic acid, gamma-linoleic acid, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), and combinations thereof.

4. The capsule according to any one of the preceding claims, wherein The at least one starch is selected from the group consisting of: cereal starches, preferably corn starch, wheat starch, rye starch, barley starch, millet starch, oat starch, rice starch; potato starch, tapioca starch, pea starch; and combinations thereof.

5. The capsule according to any one of the preceding claims, wherein The ratio of starch to fatty acid (w / w) in the layer is 15.0: 1.0 to 2.0: 1.0, preferably 10.0: 1.0 to 4.0: 1.0, particularly preferably 7.0: 1.0 to 5.0: 1.

0.

6. The capsule according to any one of claims 2 to 5, wherein The ratio (w / w) of starch, fatty acid and polyol in the layer is 15.0: 1.0: 15.0 to 2.0: 1.0: 0.1, preferably 10.0: 1.0: 10.0 to 4.0: 1.0: 0.5, particularly preferably 7.0: 1.0: 7.0 to 5.0: 1.0: 1.

0.

7. The capsule according to any one of claims 1 to 6, wherein The powder or powder mixture is selected from the group consisting of: coffee, coffee blends, coffee substitute blends, tea, tea blends, cocoa, cocoa blends, drinking chocolate, milk powder, milk coffee blends, fruit milk, vegan milk substitute, instant coffee, coffee substitute products and dry soup bases and combinations thereof.

8. A method for preparing a capsule, in particular a capsule for preparing a beverage by introducing water into said capsule, in particular a capsule according to any one of claims 1 to 7, comprising the following steps: - providing a compact prepared from a powder or a powder mixture, - applying a formulation comprising at least one starch and at least one fatty acid to the compact, wherein the at least one starch is an amylose-containing starch, - Drying the formulation to produce a coating.

9. The method according to claim 8, wherein: The preparation contains the at least one starch in a concentration of 0.5% to 20.0%, preferably 1.0% to 10.0%, particularly preferably 2.0% to 8.0%.

10. The method according to any one of claims 8 to 9, wherein: The preparation contains the at least one fatty acid in a concentration of 0.1% to 3.0%, preferably 0.2% to 2.0%, particularly preferably 0.3% to 1.0%.

11. The method according to any one of claims 8 to 10, wherein: The preparations contain at least one polyol in a concentration of 0.1% to 4.0%, preferably 0.5% to 3.0%, particularly preferably 1.0% to 2.0%.

12. The method according to any one of claims 8 to 11, wherein: The formulation is prepared by mixing the at least one fatty acid and the at least one starch simultaneously in water, preferably simultaneously with at least one polyol, followed by heating.

13. The method according to any one of claims 8 to 11, wherein: The formulation is prepared by mixing the at least one starch in water, followed by heating, followed by the addition of the at least one fatty acid and preferably at least one polyol.

14. A capsule prepared by the method according to any one of claims 8 to 13.

15. Use of a capsule according to any one of claims 1 to 7, preferably a capsule prepared by a method according to any one of claims 8 to 13, for preparing a beverage.

Citation Information

Patent Citations

  • capsule consisting of a pellet with an encasing layer

    DE102014000187B4

  • Portion containers made from wood material compounded with bioplastic

    DE102018201187B3

  • Closed cartridge for making a beverage, process and device for manufacturing such a cartridge

    EP0468079A1

  • Method for manufacturing a coffee tablet, and a coffee tablet for preparing coffee obtained with such method

    WO2008123775A1